FOOD SAFETY KNOWLEDGE AND PRACTICES ON RED AND WHITE MEATS AMONG NIGERIAN FARMING HOUSEHOLDS - ADEBAYO, OLAOLUWA (Food and Feed Research, 2023)
The relationship between farming households' knowledge and food safety practices on white and red meats is well documented in the existing scientific literature. Despite that, the population is still neutral on the knowledge and food safety practices related to white and red meats. This study intended to gain insight into the knowledge and food safety practices of the Nigerian farming households' population about white and red meat handling through a questionnaire survey. A survey was administered to a sample of selected 125 farming households' heads (42% female and 58% male) through a multi-stage sampling technique in the Wase Local Government Area, Plateau State, Nigeria. Topics covered by the questionnaire included their characteristics, knowledge and food safety practices on white and red meats. The farming households had basic knowledge of food safety (3.12) and they sometimes engaged in food safety practices on red and white meats (3.33). This survey revealed that farming households' knowledge of food safety on red and white meats was in significant positive correlation with their frequency of food safety practices on red and white meats (r = 0.297; p < 0.05). However, an advanced extension of prevailing information will help sustain farming households’ lives and promote good health in the studied area.
Keywords: meat; knowledge; food; safety; farming; households